2012
DOI: 10.1038/labinvest.2011.186
|View full text |Cite
|
Sign up to set email alerts
|

Multiple roles of the epithelium-specific ETS transcription factor, ESE-1, in development and disease

Abstract: The E26 transformation-specific (ETS) family of transcription factors comprises of 27 and 26 members in humans and mice, respectively, which are known to regulate many different biological processes, including cell proliferation, cell differentiation, embryonic development, neoplasia, hematopoiesis, angiogenesis, and inflammation. The epitheliumspecific ETS transcription factor-1 (ESE-1) is a physiologically important ETS transcription factor, which has been shown to play a role in the pathogenesis of various … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
55
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(57 citation statements)
references
References 69 publications
(147 reference statements)
1
55
0
Order By: Relevance
“…1E, right). This is consistent with AP-1 and ETS roles in mediating the inflammatory response, as both families have been implicated in responding to tumor necrosis factor alpha signaling and have been reported to induce cytokine expression in endothelial and epidermal tissues (28)(29)(30)(31)(32). At genomic regions that lose enhancer chromatin structure upon inflammation, colonic developmental transcription factor motifs predominated (KLF, HNF4, and HNF1), suggesting that these regions lose their transcription factor occupancy during colitis (33)(34)(35)(36)(37).…”
Section: Resultssupporting
confidence: 75%
“…1E, right). This is consistent with AP-1 and ETS roles in mediating the inflammatory response, as both families have been implicated in responding to tumor necrosis factor alpha signaling and have been reported to induce cytokine expression in endothelial and epidermal tissues (28)(29)(30)(31)(32). At genomic regions that lose enhancer chromatin structure upon inflammation, colonic developmental transcription factor motifs predominated (KLF, HNF4, and HNF1), suggesting that these regions lose their transcription factor occupancy during colitis (33)(34)(35)(36)(37).…”
Section: Resultssupporting
confidence: 75%
“…[37][38][39] ESE-1 (also called ELF3, ESX, jen, and ERT) is expressed in various cancer-derived cell lines, as well as in epithelial cellrich tissues, and exerts multiple roles in pathophysiological processes. [40][41][42][43] Null mutation of Elf3, the mouse homolog of human ESE-1, increases the risk of embryonic death in utero, suggesting that ESE-1 plays an important role in embryonic development. 44) Currently, in contrast, little is known about the functional significance of PEA3 and ESE-1 in differentiation, pluripotency, and tumor progression in germ cell-derived cancer cells.…”
Section: Resultsmentioning
confidence: 99%
“…E74-like factor 3 (ELF-3) belongs to the E26 transformation-specific family of transcription factors and is known to regulate epithelial cell differentiation (36). Interestingly, we found that ELF-3 level was lower in the progenitor cell populations from normal breast and tumors, and was restored mainly following E+A and EAD.…”
Section: Discussionmentioning
confidence: 99%